Rationale and institution for public-private partnerships - Jung-Wook Kim (Asian Development Bank (ADB), 2018)
Private-public partnership (PPP) methods are considered to be an effective way to narrow the gap between demand and supply of social infrastructure. If successfully pursued, PPP can deliver benefits to users, governments, and the private sector, or the so-called triple wins. Enhancing efficiency by reducing cost and time overruns is beneficial to users and governments, and better quality of service is expected via PPP. It will also examine the factors that have been important for shaping the county's PPP landscape, including fiscal soundness, unsolicited project proposals, and the refinancing and renegotiation of PPPs. PPPs are not a must-have solution but an option for building and upgrading infrastructure. In conclusion, PPPs are being promoted because it can mobilize needed resources from the private sector, maximize value for money, bring creativity and efficiency to a project, and be a source of fiscal stimulus. That said, countries should be clear on why they are promoting the PPP modality for infrastructure.
Keywords: E60; F62; H54; H81; 330; economic growth; infrastructures; public-private partnership; value for money